Biofluorescence imaging system (BIS) Guided surgery for MRONJ: A Case Series on the Preservation of Teeth and Implants - Sang-Hee Park; Yesel Kim; Hong-Cheol Yoon; Pil-Young Yun; Jeong-Kui Ku (Photodiagnosis and Photodynamic Therapy)
The decision of surgical margin for Medication-Related Osteonecrosis of the Jaw (MRONJ) surgery is challenging. Recently, a method involving biofluorescence imaging system (BIS) has been reported for its application in MRONJ surgery to live detection of pathologic bone tissue from vital bone, which cannot be distinguished during conventional surgery. This case series aimed to assess the outcomes of adjacent teeth and implants near the lesion site in MRONJ patients who underwent BIS-guided MRONJ surgery. This retrospective study was assessed the radiographic and clinical outcomes of seven patients who underwent MRONJ surgery with BIS guidance but chose not to remove adjacent teeth or implants near the lesion. A total of seven patients (1 male, 6 females, 77.2 ± 4.7 years) were included in the study. Four implants and four teeth adjacent to the lesion were preserved. Over an average duration of 8.7 months, all subjects exhibited normal soft tissue healing and function without any complications. In conclusion, the BIS guided MRONJ surgery can be considered a minimally invasive and effective approach.